Penerapan Strategi Contextual Teaching And Learning Untuk Peningkatan Kerja Keras Belajar Matematika Bagi Siswa Kelas VIII Semester Genap SMP Negeri 2 Kartasura Tahun 2012/2013 - Wibawati, Anni Nurochmah; , Prof. Dr. Sutama, M.Pd (2013)
This study aims to describe the application of Contextual Teaching and Learning strategies to increase the hard work of learning mathematics for eighth grade students of SMP Negeri 2 Kartasura. Research using Classroom Action Research. Teacher and student data sources. Data collection techniques with methods of observation, testing, field notes and documentation. Data was analyzed by comparative and interactive. Validity of the data sources and triangulation methods. The results, (1) the implementation of strategies to enhance CTL hard work learning math grade students of SMP Negeri 2 Kartasura VIIIA, (2) an increase in the hard work to learn mathematics that is: (a) students who never gave up in working on a given problem gurudari initial conditions (6, 4%), the first cycle (35.4%), 80.6% second cycle, (b) diligent in learning mathematics from baseline 9.6%, 45.1% first cycle, second cycle 83.8%, (c) earnest in completing a given task teacher from baseline 6.4%, 41.9% first cycle, second cycle 77.4%.